Enrichment of Fish Resources with Artificial Habitat in Sepunjung Lake Rantau Baru Village, Pangkalan Kerinci, Pelalawan - Utami, Niken Yufira; Putra, Ridwan Manda; Budijono, Budijono (Jurnal Perikanan dan Kelautan, 2025)
This research aims to determine the types of fish caught in Lake Sepunjung and in the Artificial Habitat equipment at Lake Sepunjung, Rantau Baru Village, Pangkalan Kerinci, Pelalawan, Riau Province. This research was conducted in January-March 2024 in Lake Sepunjung, Rantau Baru Village, Pangkalan Kerinci, Pelalawan, Riau. This research used a survey method to obtain primary data from water quality measurements and fish caught. Sampling was carried out every 2 weeks for 3 months. The results of this research obtained the value of the composition of the most common type of fish, namely the Oxgaster anomalura, with the highest percentage of 44.13%, and in Artificial Habitat, namely Ompok hypothalamus fish, with the highest percentage of 28%. The value of the diversity index (H') in Lake Sepunjung is 2.95 (moderate), and the value in Artificial Habitat is 2.83 (moderate). The value of the uniformity index (E) in Lake Sepunjung is 0.622 (low), and the value in Artificial Habitat is 0.894 (low). The value of the dominance index (C) obtained in Lake Sepunjung, namely 0.233 (low), and the value in Artificial Habitat, namely 0.165 (low)